Perjanjian Antara Pengelola Web Dengan Penjual (Studi Kasus di Situs www.lapakwongjogja.com) - Nawangsih, Raesita Dhewi; , Dr. Kelik Wardiono, S.H., M.H (2016)
The splendor of online shopping is certainly open up new opportunities in the business world, especially for the management of specialized shopping sites online. This research is conducted with the doctrinal approach. Data analysis that used is qualitative analysis. Respondent in this research is admin of lapakwongjogja. The conclusion of this research is an agreement between website manager of www.lapakwongjogja.com with the sellers has fulfilled the terms of a legal contract in Pasal 1320 KUH Perdata. Although the terms of maturity according to KUH Perdata were not being fulfilled in the purchase agreement in the sell-buy forum of Lapak Wong Jogja, it does not cause the contract becomes invalid, but it only gives a result of the agreement or the contract can be canceled by the other side, because the ability to make a bond included in subjective terms.